Like devils, but still humans: a systematic examination and moderate defense of Kant’s view of (quasi-)diabolical evil - Lu, Chao ca. 21. Jh. (International journal of philosophy and theology, 2017)
Among scholars, how to interpret and evaluate Kant’s rejection of diabolical evil remains controversial. This article has two aims. First, I will examine all six forms of (quasi-)diabolical evil either discussed by Kant or implicitly contained in his texts, thereby demonstrating the reasons why each of these forms must be rejected (or admitted) within his framework. The conclusion of this text analysis is that the extremity of human evil for Kant is quasi-diabolical Willkür which does evil for the sake of self-assertion. Second, I will offer a moderate defense of Kant’s view of (quasi-)diabolical evil as a whole. On the one hand, the legitimacy of Kant’s rejection of both diabolical Wille and full-fledged diabolical Willkür (which precludes inner conflicts between different incentives) can be confirmed within his theory of practical freedom. On the other hand, faced with the possibility of ‘occasionally doing evil qua evil’, a critical defense of Kant’s moral psychology can be established, i.e. a defense that casts doubt on the distinguishability between ‘doing evil for the sake of self-assertion’ and ‘doing evil qua evil’.